The CCTL (Cpf1-assisted Cutting and Taq DNA ligase-assisted Ligation) method for efficient editing of large DNA constructs in vitro. Issue 9 (23rd January 2017) - Lei, Chao; Li, Shi-Yuan; Liu, Jia-Kun; Zheng, Xuan; Zhao, Guo-Ping; Wang, Jin
Abstract: As Cpf1 cleaves double-stranded DNA in a staggered way, it can be used in DNA assembly. However, the Cpf1 cleavage was found to be inaccurate, which may cause errors in DNA assembly. Here, the Cpf1 cleavage sites were precisely characterized, where the cleavage site on the target strand was around the 22nd base relative to the protospacer adjacent motif site, but the cleavage on the non-target strand was affected by the spacer length. When the spacer length was 20 nt or longer, Cpf1 mainly cleaved around the 14th and the 18th bases on the non-target strand; otherwise, with a shorter spacer (i.e. 17–19 nt), Cpf1 mainly cleaved after the 14th base, generating 8-nt sticky ends. With this finding, Cpf1 with a 17-nt spacer crRNA were employed for in vitro substitution of the actII-orf4 promoter in the actinorhodin biosynthetic cluster with a constitutively expressing promoter. The engineered cluster yielded more actinorhodin and produced actinorhodin from an earlier phase. Moreover, Taq DNA ligase was further employed to increase both the ligation efficiency and the ligation accuracy of the method. We expect this CCTL (C pf1-assisted C utting and T aq DNA ligase-mediated L igation) method can be widely used in in vitro editing of large DNA constructs.